Implications and Constructions of Qur’anic in Islamic Education - Khaeril Majedi; Khoirun Nidhom; Ida Kurnia Shofa (Universitas Muhammadiyah Enrekang, 2024)
Islamic Education in Indonesia has undergone significant progress in line with the rapid development of technology. However, these developments are also part of the Western globalization strategy to spread the values of Western civilization. The impact is not only positive but also negative, even threatening the existence of Islamic educational institutions. To cope with the negative impact of globalization and the shift in values, revitalization of the values of the Quran in Islamic education is an important step. This article aims to provide a new insight into the role of Islamic education in shaping the character, morals, and achievements of pupils to support the education of future Muslim generations. It is done by exploring further the values of the Qur'an contained in Surah Al-Alaq verses 1-5. This research uses qualitative methods, a kind of library research. The approach used in this study is a phenomenological approach aimed at gaining a deep understanding, performing detailed descriptions, applying deep reductions, highlighting intersubjectivity, as well as exploring the meaning of the object of study under study. The results of the research show that based on the results of the analysis of the verses of the Qur'an, they contain fundamental values that can be a guide in the maintenance of Islamic education. Among them are humility and respect, the importance of knowledge and respect for science, independence and responsibility, and appreciation of the learning process.